Factors Affecting Psychological and Health-Related Quality-of-Life Status in Children and Adolescents with Congenital Heart Diseases - Hao-Chuan Liu; Chung-Hsien Chaou; Chiao-Wei Lo; Hung-Tao Chung; Mao-Sheng Hwang (MDPI AG, 2022)
Congenital heart disease (CHD), a severe cardiac defect in children, has unclear influences on young patients. We aimed to find the impacts of differently structure heart defects and various treatments on psychology and health-related quality of life (HRQoL) in CHD children and adolescents. CHD patients aged between 6 and 18 years old visited our hospital from 1 May 2018 to 31 September 2018, and their principal caregivers were asked to participate. We used two validated questionnaires, Children Depression Inventory-TW (CDI-TW) and Child Health Questionnaire-Parent Form 50 (CHQ-PF 50), to evaluate CHD patients' psychological and HRQoL conditions. Participants were grouped based on their cardiac defects and previous treatments. We analyzed the results via summary independent-samples t-test with post hoc Bonferroni correction and multivariant analysis. Two hundred and seventy-seven children and their principal caregivers were involved. There was no apparent depressive condition in any group. Single cardiac defect patients exhibited similar HRQoL to controls; simultaneously, those with cyanotic heart disease (CyHD), most multiple/complex CHDs children and adolescents, and those who received invasive treatments had poorer HRQoL. CyHD impacted the most on patients' psychological and HRQoL status. Patients with sole cardiac defect could live near-normal lifes; on the other hand, CyHD had the worst effects on patients' psychology and HRQoL.